European Cultures in Leo Tolstoy’s Interpretation: Ambiguous and Unambiguous (on the Basis of the Sketch “Sevastopol in May” and the Novel “War and Peace”) - Romanov, Dmitry (Slavica, 2021)
The article examines the embodiment of the interactions of Russian culture with French and German cultures in the course of global historical eventsin Tolstoy’s works. The review includes the Crimean War of 1853-1856 and the Patriotic War of 1812. The author analyzes the use of foreign language inclusions by the heroes of Tolstoyʼs works and the authorʼs assessment of them. Special attention is paid to the analysis of the ideas and images of European cultures, which help to express the worldview of the writer.